1997
DOI: 10.1001/archsurg.1997.01430320060009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Costs, Blood Products, and Operating Time in Patients Undergoing Open Heart Surgery

Abstract: Use of aprotinin at half dose in a community hospital resulted in a significant reduction in costs, blood product use, and operating room closure time in patients undergoing open heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…This is in contrast to corresponding economic studies in cardiac surgery patients [11,12,19,20]. These studies demonstrate aprotinin not only efficacious in reducing blood loss and effective in reducing allogeneic blood transfusion but also to be a cost-effective adjunct pharmacological intervention, especially when low-dose aprotinin is applied [12,19]. In the study of Baele et al [11], cost savings by aprotinin amounted to approximately 9% of the hospital bill which is far greater than savings in our orthopedic patients with approximately 2%.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This is in contrast to corresponding economic studies in cardiac surgery patients [11,12,19,20]. These studies demonstrate aprotinin not only efficacious in reducing blood loss and effective in reducing allogeneic blood transfusion but also to be a cost-effective adjunct pharmacological intervention, especially when low-dose aprotinin is applied [12,19]. In the study of Baele et al [11], cost savings by aprotinin amounted to approximately 9% of the hospital bill which is far greater than savings in our orthopedic patients with approximately 2%.…”
Section: Discussioncontrasting
confidence: 77%
“…To our knowledge, no paper has yet been published that analyzes cost data for transfusion-related cost of aprotinin administration in patients undergoing infectious orthopedic surgery. This is in contrast to corresponding economic studies in cardiac surgery patients [11,12,19,20]. These studies demonstrate aprotinin not only efficacious in reducing blood loss and effective in reducing allogeneic blood transfusion but also to be a cost-effective adjunct pharmacological intervention, especially when low-dose aprotinin is applied [12,19].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The economic analyses suggesting greater cost savings with low-dose aprotinin regimens must be tempered with the questionable effectiveness of these regimens for substantially reducing transfusion requirements and repeat surgery rates. 27,28,35 There are other considerations that must be taken into account when evaluating these economic studies. For example, the investigators did not consider possible differences in reoperation rates for bleeding, myocardial infarction, or stroke.…”
Section: Hemostatic Agents In Cardiac Surgerymentioning
confidence: 99%
“…They found that, of the two, using low dose aprotinin generated the most striking cost savings, despite being less clinically effective than the high dose alternative. Furthermore, Able and Tilly [25] found that low dose aprotinin for repeat CABG surgery saved US$1516 compared to non-treated patients; others concurred [75]. Cost savings were achieved in that there was reduced need for transfusions, reduced use of blood products, shorter pump times and reduced length of stay.…”
Section: Determining the Most Cost Effective Uses Of Aprotininmentioning
confidence: 99%